The history of Havana - Cluster, Dick, 1947- (OR Books, 2018)
"For close to 500 years, Havana has been a cultural crossroads, a meeting point for people from the Americas, Europe, and Africa. Here, in a revised and updated edition of a classic history co-written by a Cuban and an American, is the definitive chronicle of the "Pearl of the Antilles." The name of the city, write the authors, La Habana or La Havana, comes from Spanish transcriptions of an indigenous word. But in ensuing years many came to believe that the name derived from haven and harbor, which the city has always been in both a physical and a social sense. Since its founding in 1519, Havana has drawn people from all over the world, including explorers, entrepreneurs, refugees, and the exiled, to create a melting pot of influences and cultures with a very distinct history. Authors Dick Cluster and Rafael Hernández examine not only the ruptures in the city's life, but its continuities as well. The traditions that make the city unique, such as its idiosyncratic combination of territorialism and hospitality, or its proclivity for protest, reveal a drive for change as an integral element of its character. Drawing on oral histories and cultural artifacts with grace and precision, The History of Havana chronicles the city's dynamic culture and politics, making it a superbly well-rounded account of the most intriguing city in the Caribbean."--Publisher website